Pengembangan Subject Spesific Pedagogy sebagai Upaya Penguatan Profil Pelajar Pancasila pada Mata Pelajaran Matematika Fase C Sekolah Dasar - Khoironi, Dwi Rahmat; Sastrawati, Eka; Budiono, Hendra (Universitas Batanghari Jambi, 2024)
This research aims to develop subject specific pedagogy as an effort to strengthen the profile of Pancasila Students in Elementary School Phase C mathematics subjects and to determine the feasibility of subject specific pedagogy as an effort to strengthen the profile of Pancasila Students in Elementary School Phase C mathematics subjects. This research is a type of development research which is research using qualitative and quantitative approaches. The development model used in this research is the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The research was carried out at SDN 55/I Sridadi, Muara Bulian District, Batang Hari Regency with the target subjects being teachers and students. This data can be obtained through the results of validation questionnaires which are assessed by validators, namely experts, media, material experts and language experts. The results of the research show that the development of subject specific pedagogy as an effort to strengthen the profile of Pancasila students in Phase C elementary school mathematics subjects as a whole is suitable for use in the learning process in elementary schools.